(untitled) (Okhaldhunga Journal, 2025)
This paper explores the concept of public archaeology, using an example of a case study of Bhajya Pukhu, a historic pond in Bhaktapur, Nepal. Public archaeology involves the community, educates people, and makes archaeological knowledge open to everyone. It helps bridge the gap between academic research and public understanding. The study shows how public archaeology helps preserve and revive its cultural identity, focusing on the restoration of Bhajya Pukhu. The project used community involvement, traditional restoration methods using local resources, and discovered important artifacts during excavation. It highlights sustainability, inclusivity, and ethical practices in public archaeology. By looking at trends like public engagement, new technologies, and managing cultural heritage, the study emphasizes the importance of community participation in preserving historical sites. The case of Bhajya Pukhu shows that public archaeology not only brings cultural heritage back to life but also strengthens community identity and connects people to their past. This research highlights how public archaeology can protect cultural heritage for future generations.